2021
DOI: 10.3390/nano11040888
|View full text |Cite
|
Sign up to set email alerts
|

Hard and Soft Protein Corona of Nanomaterials: Analysis and Relevance

Abstract: Upon contact with a biological milieu, nanomaterials tend to interact with biomolecules present in the media, especially proteins, leading to the formation of the so-called “protein corona”. As a result of these nanomaterial–protein interactions, the bio-identity of the nanomaterial is altered, which is translated into modifications of its behavior, fate, and pharmacological profile. For biomedical applications, it is fundamental to understand the biological behavior of nanomaterials prior to any clinical tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 132 publications
2
72
0
Order By: Relevance
“…In agreement with the report by Ogawara et al [ 22 ] that the surface modification of NPs with albumins suppressed the adsorption of opsonins, our results strongly suggest that the surface modification of NPs with PAR-containing peptides is effective for preventing the uptake by Kupffer cells, which in turn recruits serum albumins onto the surface of NPs and prevents them from opsonization. It has been known that protein corona formation on the surface of NPs may play a significant role on the pharmacokinetics [ 32 , 33 , 34 ]. Our results suggested that surface modification of NPs with PAR-containing peptide may affect the protein corona formation; however, further investigation is needed.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with the report by Ogawara et al [ 22 ] that the surface modification of NPs with albumins suppressed the adsorption of opsonins, our results strongly suggest that the surface modification of NPs with PAR-containing peptides is effective for preventing the uptake by Kupffer cells, which in turn recruits serum albumins onto the surface of NPs and prevents them from opsonization. It has been known that protein corona formation on the surface of NPs may play a significant role on the pharmacokinetics [ 32 , 33 , 34 ]. Our results suggested that surface modification of NPs with PAR-containing peptide may affect the protein corona formation; however, further investigation is needed.…”
Section: Resultsmentioning
confidence: 99%
“…capable of selectively reacting with designated blood proteins. The modulation of the contents of the corona by surface functionalization is an established fact [25][26][27][28][29][30][31][32][33][34]53]. Thus, we propose that the antibacterial efficacy of a metal-based nanoparticle, in the human body, is due to protein corona-bacterium interactions.…”
Section: The Exceptional Antibacterial Efficacy Of Nanoparticle Alloysmentioning
confidence: 95%
“…Although papers identifying nanoparticle corona proteins that were adsorbed from protein-containing liquids, such as blood and plasma, are rather scarce, several [25][26][27][28][29][30][31][32][33][34] do exist. A number of points that are important to the present discussion can be gleaned from them:…”
Section: The Protein Coronamentioning
confidence: 99%
“…For this, the particles were immersed in 1 mg/mL COOH-PEG-SH for 3 h to increase the negative surface charge and make a protein corona formation preventing layer. 32,33 Core−Shell Microparticle Characterization. Potential aggregation was assessed by examining the synthesized particles with optical microscopy (Zeiss Axioscope 2).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In the last step, the particles were modified with thiol-terminated poly­(ethylene glycol) to reduce their specificity to biological molecules, particularly proteins. For this, the particles were immersed in 1 mg/mL COOH-PEG-SH for 3 h to increase the negative surface charge and make a protein corona formation preventing layer. , …”
Section: Methodsmentioning
confidence: 99%